207k views
2 votes
Graph the function. y = -x^2 - 6x - 3

Graph the function. y = -x^2 - 6x - 3-example-1
User Walucas
by
5.9k points

1 Answer

4 votes

ANSWER and EXPLANATION

To graph the equation given, we have to find values of y for certain values of x.

Let us pick x to be:


x=-5,-4,-3,-2,-1

When x = -5:


\begin{gathered} y=-(-5)^2-6(-5)-3 \\ y=2 \end{gathered}

When x = -4:


\begin{gathered} y=--(-4)^2-6(-4)-3 \\ y=5 \end{gathered}

When x = -3:


\begin{gathered} y=-(-3)^2-6(-3)-3 \\ y=6 \end{gathered}

When x = -2:


\begin{gathered} y=-(-2)^2-6(-2)-3 \\ y=5 \end{gathered}

When x = -1:


\begin{gathered} y=-(-1)^2-6(-1)-3 \\ y=2 \end{gathered}

Now, we have a table of values for the graph of the equation:

Now, plot the graph:

That is the graph of the equation.

Graph the function. y = -x^2 - 6x - 3-example-1
Graph the function. y = -x^2 - 6x - 3-example-2
User David Pointer
by
6.2k points